Molecular characterization of MAP9 in the photoreceptor sensory cilia as a modifier in canine RPGRIP1-associated cone-rod dystrophy - Takahashi, Kei; Kwok, Jennifer C.; Sato, Yu; Aguirre, Gustavo D.; Miyadera, Keiko (Frontiers in Cellular Neuroscience, 2023)
Photoreceptors possess a highly specialized primary cilium containing expanded ciliary membrane discs called the outer segment. The photoreceptor cilium is essential for the maintenance of the outer segment, and pathogenic variants in more than 50 cilia-related genes have been identified as causing non-syndromic inherited retinal diseases in patients. The retinitis pigmentosa GTPase regulator interacting protein 1 (RPGRIP1) is a structural protein localized to the photoreceptor cilium and biallelic RPGRIP1 variants have been associated with non-syndromic human inherited retinal diseases. In a canine cone-rod dystrophy model, a naturally occurring 44-bp exonic insertion in RPGRIP1 (RPGRIP1ins44/ins44) is the primary disease locus while an additional homozygous variant in MAP9 (microtubule associated protein 9) (MAP9aff/aff) acts as a modifier associated with early disease onset. MAP9 was originally identified as a microtubule-binding protein stabilizing microtubule structure during both mitosis and interphase in human cell lines. However, the roles of MAP9 in primary cilia, including photoreceptor neurosensory cilia, have not been well understood. Hence, we characterized the pathogenic phenotypes associated with homozygous MAP9 variant, and investigated the molecular function of MAP9 in primary cilia using the RPGRIP1-associated oligogenic canine cone-rod dystrophy model as well as cultured cells. Both functionally and structurally, the RPGRIP1ins44/ins44MAP9aff/aff retina exhibited progressive cone photoreceptor degeneration starting earlier than the retina affected by RPGRIP1ins44/ins44 alone. Based on immunostaining of canine retinal sections and cultured cells, we found that MAP9 is prominently localized in the basal body of primary cilia and played an important role in maintaining the structure of ciliary microtubule axoneme. These findings suggest that the affected MAP9, together with mutant RPGRIP1, is deprived of critical roles in cilia organization and maintenance resulting in altered cilia structure and function giving rise to early onset and accelerated disease progression in the RPGRIP1ins44/ins44MAP9aff/aff double homozygote cone-rod dystrophy canine model.